Strategi Komunikasi Pemasaran Suweg Lapis Genggong Dalam Peningkatan Daya Jual di Kecamatan Maron Kabupaten Probolinggo - Ahmad Faqih Zainuri (Medio Jurnal Ilmu Komunikasi, 2023)
The title of this study is "Marketing Communication Strategy of Suweg Lapis Genggong in Increasing Selling Power in Maron District, Probolinggo Regency (Descriptive Study of Instagram Digital Marketing of Suweg Lapis Genggong Products). In the current era, the development of technology and information is fast and significant so that it can be used by anyone at any time with creative and innovative works. It can be used to communicate with anyone without a time limit. Along with the development of time, there is a term, namely new media or what we often call new media, this is very interesting because it can be used to convey information more easily. An example of this new media is the emergence of various social media, one of which is Instagram. nstagram so that Instagram social media has become one of the favorite social media. As for the benefits of Instagram social media, in addition to conveying various kinds of information, it can also be used as a means of promotion and publication of a product, as an example of this Suweg lapis genggong product which has used Instagram social media as access in digital The title of this study is "Marketing Communication Strategy of Suweg Lapis Genggong in Increasing Selling Power in Maron District, Probolinggo Regency (Descriptive Study of Instagram Digital Marketing of Suweg Lapis Genggong Products). In the current era, the development of technology and information is fast and significant so that it can be used by anyone at any time with creative and innovative works. It can be used to communicate with anyone without a time limit. Along with the development of time, there is a term, namely new media or what we often call new media, this is very interesting because it can be used to convey information more easily. An example of this new media is the emergence of various social media, one of which is Instagram. nstagram so that Instagram social media has become one of the favorite social media. As for the benefits of Instagram social media, in addition to conveying various kinds of information, it can also be used as a means of promotion and publication of a product, as an example of this Suweg lapis genggong product which has used Instagram social media as access in digital marketing because on social media Instagram there are interesting features that can help Suweg lapis genggong products to convey product information quickly and broadly to the public. The purpose of this research is to find out the communication strategy marketing of digital products and digital marketing based on Instagram as well as increasing the selling power of Suweg lapis genggong products. The research method used is communicative descriptive research method with data collected through direct and indirect interviews, observation and structured documentation as well as study literature, namely by looking at previous research. The expected results of this research are as social media Instagram can be used to convey messages or exchange marketing because on social media Instagram there are interesting features that can help Suweg lapis genggong products to convey product information quickly and broadly to the public. The purpose of this research is to find out the communication strategy marketing of digital products and digital marketing based on Instagram as well as increasing the selling power of Suweg lapis genggong products. The research method used is communicative descriptive research method with data collected through direct and indirect interviews, observation and structured documentation as well as study literature, namely by looking at previous research. The expected results of this research are as social media Instagram can be used to convey messages or exchange